2016
DOI: 10.1186/s13633-016-0036-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a long-term growth hormone treatment on lipid and glucose metabolism: a randomized trial in short Japanese children born small for gestational age

Abstract: BackgroundLong-term growth hormone (GH) treatments in short children born small for gestational age (SGA) restore lipid metabolism, but also increase insulin resistance. The aim of this study was to evaluate the influence of long-term GH therapy on lipid and glucose metabolism as well as its dose dependency in short Japanese children born SGA.MethodsEighty Japanese children with a short stature who were born SGA participated in this study; 65 were treated with fixed GH doses of 0.033 (low) or 0.067 (high) mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 19 publications
5
16
0
Order By: Relevance
“…Our findings are consistent with the reports by Horikawa et al. and Tanaka et al who have also reported similar results for the effects of rhGH treatment in patients with SGA short stature in Japan ( 15 , 16 ). Considering the present and previous results, it is assumed that rhGH treatment does not impose a particular risk for the development of type 2 diabetes, although rhGH treatment caused a slight increase in the glucose tolerance-related parameters based on insulin resistance.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our findings are consistent with the reports by Horikawa et al. and Tanaka et al who have also reported similar results for the effects of rhGH treatment in patients with SGA short stature in Japan ( 15 , 16 ). Considering the present and previous results, it is assumed that rhGH treatment does not impose a particular risk for the development of type 2 diabetes, although rhGH treatment caused a slight increase in the glucose tolerance-related parameters based on insulin resistance.…”
Section: Discussionsupporting
confidence: 94%
“…Horikawa et al . reported that they did not find any adverse effects on glucose metabolism in a clinical trial in Japanese children with SGA short stature ( 15 ). In this study, we also found that HbA1c, fasting blood glucose levels, IRI levels, and the sigma IRI of the OGTT were higher during treatment than before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies revealed that insulin sensitivity and β-cell function in SGA individuals improved after GH treatment and no adverse metabolic events developed in rodents and humans [19,30]. Other studies showed that SGA children exhibited higher fasting insulin levels and elevated HOMA-IR over time with GH treatment, while after discontinuation of GH, serum insulin levels returned to normal age-related levels [27,31]. In our study, SGA rats ▶Fig.…”
Section: Discussionsupporting
confidence: 56%
“…GH performs a wide range of roles and exhibits a significant effect on glucose and lipid metabolism. Many studies conducted in SGA children showed that long-term continuous GH treatment does not adversely affected glucose metabolism parameters, but also might have a potentially beneficial effect on several parameters in lipid metabolism [26][27][28]. In parallel, our previous study showed that GH treatment normalized serum triglycerides in SGA rats in adulthood [29].…”
Section: Discussionmentioning
confidence: 70%
“…Serum cholesterol level is the main readout for the lipid profile evaluation to determine the risk of cardiovascular events in the SGA population, and GH treatment of SGA children was reported to improve the patients' cholesterol profiles in several studies [6,11,19]. Apolipoproteins, the protein constituents of lipoprotein particles, were recently reported to be superior to cholesterol for estimating the risk of cardiovascular events [20][21][22].…”
mentioning
confidence: 99%